Les Élections Législatives Grecques du 9 Avril 2000 - Catsiapis, Jean (Études helléniques / Hellenic Studies, 2000)
Greece’s PASOK (panhellenic Socialist Movement), governed from 1981 to 1989, was returned to office in 1993 and 1996. The party won the April 9 elections after a close race. This last victory is primarily that of Prime Minister Costas Simitis, who took over from Andreas Papandreou, as head of government in January 1996 and as leader of PASOK in June 1996. What follows is a succinct review of the April elections including the campaign, voting patterns and expectations of the Greek People.